Distribution of various histopathological patterns of ovarian lesions in different age groups - Ayesha Imtiaz Malik, Farrukh Kamal, Munazza Iqbal, Aasmaa Qureshy, Farah Kalsoom (Pakistan Journal of Medical & Health Sciences, 2022)
The spectrum of ovarian pathologies embraces wide age range among females because the risk of developing ovarian lesion starts from birth and follows diverse patterns through-out the life.1,2 The rate of development of complications, recurrence, progression to malignancy, morbidity and mortality, also varies according to the age of presentation of various ovarian pathologies.3,4,5 The prevalence of cystic lesions of ovary is more in reproductive age group as compared to post-menopausal women.6,7 Malignant neoplasms have more been observed in an advanced age group.8,9,10 The current study is aimed to observe the distribution of various histopathological patterns of ovarian lesions in different age groups. This study may be beneficial in stratifying patients, into different risk based groups and prognosis associated groups, depending upon the age of patient at the time of presentation. Methods: Total 150 cases of ovarian lesions were selected by convenient sampling in current descriptive study, carried out at Pathology department of Fatima Jinnah Medical University, Lahore from May, 2019 till June, 2020. Routine H & E stained sections, from specimens of total abdominal hysterectomy with unilateral or bilateral salpingo-oophorectomy, unilateral or bilateral oophorectomy and salpingo-oophorectomy procedures, done either for primary ovarian lesion or other than primary ovarian pathology, in all age groups, were included. Results: A majority of ovarian lesions 123 (82%) were observed in the reproductive age group, mostly being non-neoplastic (89.5%). Out of 19 post-menopausal patients, 12 presented with malignant neoplasms. All patients belonging to pre-pubertal age group had non-neoplastic pathologies. Conclusion: The malignant ovarian tumors are prevalent in post-menopausal patients while reproductive age group predominantly exhibits non-neoplastic and benign ovarian lesions. The pre-pubertal age group commonly present with non-neoplastic ovarian pathologies. Keywords: Histopathological patterns of ovarian lesion, Malignant ovarian tumors, Reproductive age group.